PENGARUH GUIDED IMAGERY DALAM MENURUNKAN STRESS SISWA MENGHADAPI PROSES BOARDING SCHOOL DI SMK KESDAM IV KOTA MAGELANG - Sugiyanti, Desi Ari; Suhariyanti, Enik; Priyanto, Sigit (Journal Of Holistic Nursing Science, 2017)
Adolescence is a period of transition from childhood to adulthood. In adolescence can also be called the period of "storms and stresses" a period in which emotional tension increases as a result of physical changes and glands. Stress in schools arises from the various uncomfortable pressures felt by students, thus triggering physical and psychological tensions that result in changing behavior and affecting students own learning achievements cognitively. To know the effect of guided imagery in reducing stress level of students in facing Boarding school process at SMK Kesdam IV/Diponegoro Magelang City. The research design used in this research is Quasi Experiment with two group type pre post test with control group, the analysis used is paired-samples t-test. Guided imagery influence on decreasing stress level in students who experience boarding school process at SMK Kesdam IV / Diponegoro with p-value = 0,000 with mean of decrease 4,83 compared to control group with mean of decrease 2,37. The level of stress on the boarding school process can go down with guided imagery